Pulmonary Hypertension in Heart Failure with Preserved Ejection Fraction: A Community-Based Study - Lam, Carolyn S.P. (2009)
OBJECTIVES: To define the prevalence, severity and significance of pulmonary hypertension (PH) in heart failure with preserved ejection fraction (HFpEF) in the general community. BACKGROUND: While HFpEF is known to cause PH, its development is highly variable. Population-based data are lacking, and the relative contribution of pulmonary venous versus pulmonary arterial hypertension to PH in HFpEF is unknown. We hypothesized that PH would be a marker of symptomatic pulmonary congestion, distinguishing HFpEF from preclinical hypertensive heart disease (HTN). METHODS: Population-based study of 244 HFpEF patients (76±13y; 45%male) followed from Doppler echocardiography over 3 years. Controls were 719 adults with HTN without HF (66±10y; 44%male). Pulmonary artery systolic pressure (PASP) was derived from the tricuspid regurgitation velocity and PH defined as PASP>35 mmHg. Pulmonary capillary wedge pressure (PCWP) was estimated from E/e’. RESULTS: In HFpEF, PH was present in 83% and median (25(th), 75(th) percentile) PASP was 48 (37, 56) mmHg. PASP increased with PCWP (r=0.21; p<0.007). Adjusting for PCWP, PASP was higher in HFpEF than HTN (p<0.001). PASP distinguished HFpEF from HTN with an area under receiver-operating curve of 0.91 (p<0.001) and strongly predicted mortality in HFpEF (hazard ratio=1.3 per 10 mmHg; p<0.001). CONCLUSIONS: PH is highly prevalent and often severe in HFpEF. While pulmonary venous hypertension contributes to PH, it does not fully account for the severity of PH in HFpEF, suggesting that a component of pulmonary arterial hypertension also contributes. The potent effect of PASP on mortality lends support for therapies aimed at pulmonary arterial hypertension in HFpEF.